Operationalizing a Framework for Assessing the Enabling Environment for Community Forest Enterprises: A Case Study from Nepal - Sharma, B.P.; Lawry, S.; Paudel, N.S.; McLain, R.; Adhikary, A.; Banjade, M.R. (Springer, 2020)
We demonstrate how Baynes et al.’s (Glob Environ Change 35:226–238, 2015. 10.1016/j.gloenvcha.2015.09.011) framework can be operationalized as a tool for identifying potential intervention points for supporting the tenure and governance-enabling environment for CFEs. We do so by applying the framework to a sample of CFUG-managed CFEs in Nepal to see how they measure up as a group with respect to the five success factors. Our study suggests that for CFEs to thrive, they will require policy and legal frameworks that devolve commercial harvesting rights to economically valuable products, and provision of processing locations and licensing practices that are not overly restrictive. The findings will be useful not only for Nepal, but for many other countries dependent on forests for their economic development and whose inhabitants rely on forests for their livelihoods.